The impact of reclassifying cancers of unspecified histology on international differences in survival for small cell and non‐small cell lung cancer (ICBP SurvMark‐2 project). Issue 5 (20th May 2021) - Morgan, Eileen; Arnold, Melina; Rutherford, Mark J.; Bardot, Aude; Ferlay, Jacques; De, Prithwish; Engholm, Gerda; Jackson, Christopher; Little, Alana; Saint‐Jacques, Nathalie; Walsh, Paul; Woods, Ryan R.; et al.
Abstract: Survival from lung cancer remains low, yet is the most common cancer diagnosed worldwide. With survival contrasting between the main histological groupings, small‐cell lung cancer (SCLC) and non‐small cell lung cancer (NSCLC), it is important to assess the extent that geographical differences could be from varying proportions of cancers with unspecified histology across countries. Lung cancer cases diagnosed 2010‐2014, followed until 31 December 2015 were provided by cancer registries from seven countries for the ICBP SURVMARK‐2 project. Multiple imputation was used to reassign cases with unspecified histology into SCLC, NSCLC and other. One‐year and three‐year age‐standardised net survival were estimated by histology, sex, age group and country. In all, 404 617 lung cancer cases were included, of which 47 533 (11.7%) and 262 040 (64.8%) were SCLC and NSCLC. The proportion of unspecified cases varied, from 11.2% (Denmark) to 29.0% (The United Kingdom). After imputation with unspecified histology, survival variations remained: 1‐year SCLC survival ranged from 28.0% (New Zealand) to 35.6% (Australia) NSCLC survival from 39.4% (The United Kingdom) to 49.5% (Australia). The largest survival change after imputation was for 1‐year NSCLC (4.9 percentage point decrease). Similar variations were observed for 3‐year survival. The oldest age group had lowest survival and largest decline after imputation. International variations in SCLC and NSCLC survival are only partially attributable to differences in the distribution of unspecified histology. While it is important that registries and clinicians aim to improve completeness in classifying cancers, it is likely that other factors play a larger role, including underlying risk factors, stage, comorbidity and care management which warrants investigation. Abstract : What's new? Survival in lung cancer varies considerably between the two main histological subtypes of small‐cell and non‐small cell lung cancer across countries. Variations in the proportion of lung cancer cases with unspecified histology however limit international comparisons of subtype‐specific survival. Using high‐quality population data on 404, 617 lung cancer cases in seven countries, here the authors found that survival varied across countries for both subtypes (by up to 8.1% points). International survival disparities by histological subtype remained after assigning unspecified cases, suggesting that survival differences are likely due to other factors such as stage at diagnosis and comorbidity.